Pharmacological Interactions in Patients with Epileptic Crisis Hospitalized in a Public Institution - Montiel, Carolina Soledad (2020)
Objective: The present study was carried out to evaluate the potential pharmacological interactions in a group of adult hospitalized patients due to an epileptic crisis. Methodology: Descriptive-analytical study. Data was obtained from medical records of hospitalized patients during the investigation period. Results: 937 patients were enrolled in the study, 143 different drug interactions were detected in 35 patients, which involved 46 medicines administered. The interactions were classified according to their theoretical relevance in serious (18.88%), significant (51.04%) and minor (30.07%). 48.57% of patients presented drug interactions with nutrients. Conclusion: The intervention of a multidisciplinary team is necessary for the management of these patients, which includes nutritionists specially trained in aspects of pharmacokinetics and pharmacodynamics, in order to minimize the incidence of pharmacological interactions.